Savings Of Low Income Households In Northern States Of Malaysia - Mohd Shakil, Nurul Syifaa (2020)
The first objective of this study is to assess the amount of household savings with different savings measurements in Malaysia. The second objective is to analyse the determinants of household savings in Malaysia. The third objective is to assess the savings mechanism used by the low income households in the Northern States of Malaysia. The last objective of this study is to assess the impact of risks and other factors towards the savings of low income households in the northern states of Malaysia.